Silicon poisoning resistant catalyst and preparation method thereof
By loading MnOx-CeO2-CuO transition metal oxide on a three-dimensional mesh ceramic fiber cotton support, the problem of silicon poisoning in the oxidation process of organosilicon compounds is solved, and the efficient durability and economic benefits of the catalyst are achieved.
Patent Information
- Application Number
- CN202510372111.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
Traditional catalysts are susceptible to silicon poisoning during the oxidation of organosilicon compounds, resulting in the coverage of the active sites of the catalyst, insufficient service life, and nanocatalysts are prone to deactivate at high temperatures.
Three-dimensional mesh ceramic fiber cotton is used as a carrier, and Al2O3-SiO2-ZrO2 composite oxide support is formed by aging treatment of zirconium acetate solution. Then, vacuum drying and calcining is carried out in a mixed solution of manganese nitrate and cerium nitrate to form a MnOx-CeO2 primary active layer, and then MnOx-CeO2-CuO transition metal oxide supported on the fiber surface is activated by copper sol pressure-keeping treatment and drying.
The catalyst's tolerance to silicon poisoning is improved, the silicon deposition capacity is increased, and the fiber mesh structure realizes dynamic interception and capacity buffering of silicon deposits, extending the service life of the catalyst, which can reach more than 5 times that of traditional catalysts.
Smart Images

Figure CN119869550A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a silicon poisoning-resistant catalyst and a preparation method thereof. Background Art
[0002] In the manufacture of organosilicon compounds, substances such as siloxane, isopropanol, methyl chloride, and methanol will volatilize or be generated during the chemical reaction stages such as synthesis and polycondensation. For example, organic compounds such as siloxane volatilize due to the high temperature conditions of the polymerization reaction. Organosilicon waste gas contains volatile organic compounds (VOC s ), chlorine, silane and other harmful substances, which may cause respiratory irritation, skin allergies and other problems. Long-term exposure to such waste gas may cause chronic damage to the nervous system, liver and kidneys, and even increase the risk of cancer. Silicone evaporates faster in high temperature environments and may enter the human body through the air, causing symptoms such as headaches, insomnia, and decreased liver and kidney function.
[0003] During the catalytic oxidation process, organosilicon compounds will generate SiO2 deposition, resulting in the covering of the active sites of the catalyst (called silicon poisoning). For traditional catalysts such as Pt honeycomb catalysts, the specific surface area of honeycomb ceramics as carriers is usually less than 50㎡ / g, and silicon deposits easily clog the pores, resulting in the service life of the catalyst often being less than 200 hours. Those skilled in the art have made further explorations on this, using ceramic fibers as carriers, and taking advantage of the large specific surface area and high porosity of fiber cotton. For example, the publication number CN103806990A discloses a method for preparing a ceramic fiber catalyst carrier for an automobile exhaust processor, wherein inorganic salts of cerium, zirconium, lanthanum, strontium and cobalt are added to distilled water, and stirred evenly to obtain a catalyst aqueous solution. A sol forming agent is added to the catalyst aqueous solution, stirred evenly, and then a colloidal suspension agent is added to obtain a stable catalyst sol. The ceramic fiber cotton column is immersed in the catalyst sol to obtain a ceramic fiber cotton column with a catalyst colloid adhered to the surface; then the ceramic fiber cotton column carrying the catalyst is obtained by drying and calcining, and is loaded into a metal shell with an inner insulation layer to obtain an automobile exhaust purifier. This patented technology has achieved certain results by using ceramic fiber as a carrier compared to honeycomb ceramic as a carrier. However, the simple impregnation process easily results in a loose bonding between the catalyst and the ceramic fiber. Therefore, high-temperature sintering at 800 to 1200 degrees is required to obtain a better loading effect. However, the nanocatalyst is prone to high-temperature deactivation at 800 to 1200 degrees, resulting in a decrease in catalytic performance and a poor service life of the catalyst. Summary of the invention
[0004] In view of the defects in the prior art, the object of the present invention is to provide a silicon-poisoning-resistant catalyst and a preparation method thereof.
[0005] A method for preparing a silicon-poisoning resistant catalyst provided by the present invention comprises: S1, immersing high-aluminum ceramic fiber cotton in a zirconium acetate solution for aging treatment, filtering, drying, and calcining to form a three-dimensional mesh ceramic fiber cotton carrier composed of Al2O3-SiO2-ZrO2 composite oxide; S2, placing the carrier prepared in step S1 in a mixed solution of manganese nitrate and cerium nitrate, vacuum drying and calcining to form an intermediate, wherein the intermediate is MnO loaded on the fiber surface. x -CeO2 carrier for the primary active layer; S3, placing the intermediate prepared in step S2 in a sealed container, evacuating the container, injecting copper sol and maintaining pressure, removing excess sol on the surface of the intermediate by centrifugation, and then drying and activating the intermediate to form a three-dimensional mesh ceramic fiber cotton fiber surface loaded with transition metal oxide structure, wherein the transition metal oxide is MnO x -CeO2-CuO.
[0006] In some embodiments, in step S1, nitric acid is added to the zirconium acetate solution as a hydrolysis catalyst.
[0007] In some embodiments, in step S1, the fiber diameter in the carrier is 3-10 μm, the porosity is ≥85%, and the BET specific surface area is 200-500 m² / g; In some implementations, in step S1, the mass ratio of aluminum to silicon in the high-aluminum ceramic fiber wool is 6:3.
[0008] In some embodiments, in step S1, the mass ratio of aluminum, silicon and zirconium in the carrier is 6:3:1.
[0009] In some embodiments, in step S2, manganese nitrate (Mn(NO3)2·4H2O) and cerium nitrate (Ce(NO3)3·6H2O) are mixed at a molar ratio of Mn:Ce=4:1 and then prepared into a solution with deionized water.
[0010] In some embodiments, in step S3, the copper sol is a transparent sol formed by dissolving Cu(NO3)3·3H2O and citric acid in ethanol at a molar ratio of 1:1.2 and refluxing at a predetermined temperature.
[0011] In some embodiments, in step S3, drying activation is performed as follows: the intermediate from which excess sol is removed is dried at 120°C for 2 hours, then heated to 600°C at a rate of 5°C / min, and reduced in a mixture of hydrogen and nitrogen for 2 hours, wherein the volume ratio of hydrogen in the mixture of hydrogen and nitrogen is 5%.
[0012] The present invention also provides a silicon-poisoning resistant catalyst, comprising a transition metal oxide supported on a carrier; The transition metal oxide is MnOx -CeO2-CuO, the mass fraction of the transition metal oxide is 15-20%; The carrier is a three-dimensional mesh ceramic fiber cotton composed of Al2O3-SiO2-ZrO2 composite oxide, the fiber diameter of the three-dimensional mesh ceramic fiber cotton is 3-10 μm, the porosity is ≥85%, and the BET specific surface area is 200-500 m2 / g.
[0013] In some embodiments, the mass ratio of aluminum, silicon and zirconium in the carrier is 6:3:1.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The structure of the catalyst prepared by the present invention is that the fiber surface of the three-dimensional mesh ceramic fiber cotton is loaded with transition metal oxides. The fiber surface catalyst preferentially converts organic silicon into silicon dioxide particles with a particle size of 0.1-1 μm, and uses a large specific surface area to provide a silicon deposition capacity that is 5-10 times that of traditional catalysts. At the same time, the fiber mesh structure has a filtration interception rate of more than 90% for silicon deposits, which realizes dynamic interception and capacity buffering of silicon deposits, and improves the performance of the catalyst as a pre-treatment agent. When the catalyst treats monosilane waste gas at 350°C, the service life can reach more than 5 times that of traditional catalysts, and has significant economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 It is a comparison chart of the catalytic performance of the silicon-poisoning resistant type of the present invention and the catalytic performance of the honeycomb ceramic carrier; Figure 2 This is a schematic diagram of the electron microscope structure of the three-dimensional mesh ceramic fiber wool of the present invention; Figure 3 This is a schematic diagram of the electron microscope structure of the transition metal oxide of the present invention loaded on the fiber surface. DETAILED DESCRIPTION
[0016] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention. Example
[0017] This embodiment provides a method for preparing a silicon-poisoning resistant catalyst, comprising the following steps: S1, preparation of a three-dimensional ceramic fiber cotton carrier, including precursor sol soaking and high-temperature calcination, wherein: Precursor sol immersion specifically includes: S1-1, dissolving zirconium acetate Zr(OCH2CH3)4 in deionized water to form a solution with a concentration of 10 wt%, adding 0.1 mol / L nitric acid as a hydrolysis catalyst, and stirring magnetically for 30 min; S1-2, immersing high-aluminum ceramic fiber wool with a mass ratio of aluminum to silicon of 6:3 into the solution prepared in step S1-1, aging at 60° C. for 12 hours, filtering, and drying to form a precursor. In this embodiment, the average fiber diameter of the high-aluminum ceramic fiber wool is about 5 μm.
[0018] The high temperature calcination procedure specifically includes: S1-3, the precursor prepared in step S1-2 is first heated to 600°C at 2°C / min and kept for 2 hours, and then heated to 1200°C at 5°C / min and kept for 4 hours, to obtain a three-dimensional mesh ceramic fiber cotton carrier composed of Al2O3-SiO2-ZrO2 composite oxide. The mass ratio of aluminum, silicon and zirconium in the prepared carrier is 6:3:1, the fiber diameter of the prepared carrier is 3 to 10 μm, the porosity is ≥85%, and the BET specific surface area is 200 to 500 m2 / g.
[0019] S2, preparation of intermediates, specifically including: S2-1, manganese nitrate (Mn(NO3)2·4H2O) and cerium nitrate (Ce(NO3)3·6H2O) were mixed at a molar ratio of Mn:Ce=4:1, and prepared into a 0.5 mol / L solution with deionized water; S2-2, immersing the support prepared in step S1 into the solution formed in step S2-1, ultrasonically treating at a power of 200 W for 30 min, and then vacuum drying at a temperature of 80° C. for 6 h; S2-3, heating the structure prepared in step S2-2 to 400°C at a rate of 3°C / min and then keeping the temperature for 3 hours to form an intermediate, wherein the intermediate is a three-dimensional mesh ceramic fiber cotton carrier with MnO loaded on the fiber surface. x -CeO2 primary active layer structure.
[0020] S3, carrier-loaded transition metal oxide, specifically comprising: S3-1, dissolve Cu(NO3)3·3H2O and citric acid in ethanol at a molar ratio of 1:1.2, and reflux at 60°C for 4 h to form a transparent sol; S3-2, placing the intermediate prepared in step S2 in a sealed container, evacuating to -0.08 MPa, injecting the copper sol prepared in step S3-1, and maintaining the pressure for 30 min; S3-3, centrifuging the carrier prepared in step S3-2 at a speed of 2000 rpm for 2 min to remove excess sol on the surface of the intermediate; S3-4, drying the intermediate with copper sol on the surface prepared in step S3-3 at 120°C for 2h, then heating to 600°C at a rate of 5°C / min, and reducing in a mixture of hydrogen and nitrogen for 2h, wherein the volume proportion of hydrogen in the mixture of hydrogen and nitrogen is 5%, to form a three-dimensional mesh ceramic fiber cotton structure with a transition metal oxide loaded on the fiber surface, wherein the transition metal oxide is MnO x -CeO2-CuO, the loading amount is about 18wt%. Example
[0021] In this embodiment 2, the preparation steps of the three-dimensional ceramic fiber wool carrier are the same as those of the embodiment 1, except that the loading step of the transition metal oxide adopts a one-time impregnation molding method, specifically: S1: This step is the same as step S1 in Example 1, and its process will not be repeated here.
[0022] S2-1, manganese nitrate (Mn(NO3)2·4H2O) and cerium nitrate (Ce(NO3)3·6H2O) were mixed at a molar ratio of Mn:Ce=4:1, and a 0.5 mol / L catalyst solution was prepared with deionized water; S2-2, a transparent sol formed by dissolving Cu(NO3)3·3H2O and citric acid in ethanol at a molar ratio of 1:1.2 and refluxing at 60°C for 4 hours is added to the catalyst solution prepared in step S2-1 and stirred to form a sol; S2-3, placing the three-dimensional mesh ceramic fiber cotton carrier prepared in step S1 into the sol in step S2-2, and soaking for 3-5 hours to obtain a three-dimensional mesh ceramic fiber cotton with a catalyst colloid adhered to the surface; S2-4, heat-treating the three-dimensional mesh ceramic fiber cotton with the catalyst colloid adhered to the surface in step S2-3 to obtain a three-dimensional mesh ceramic fiber cotton loaded with a catalyst, wherein the catalyst is a transition metal oxide, and the transition metal oxide is MnO x -CeO2-CuO, the loading amount is about 18wt%.
[0023] The process of this comparative example is the same as that of step S2 in embodiment 2, except that in step S1 of this comparative example, the carrier is a honeycomb ceramic, and the honeycomb ceramic is 200 mesh cordierite.
[0024] Test conditions: dimethylsilane concentration 1000ppm, air velocity 10000h -1 , temperature 350℃ Test results: See Table 1 and Appendix Figure 2: Table 1 Test items Example 1 Example 2 Comparative Example Initial conversion rate (350℃) 98.2% 97.8% 98.5% Conversion rate after 1000h 95.1% 77.3% <40% Silicon deposition capacity 21.7 g / 100g catalyst 20.3 g / 100g catalyst 3.2 g / 100g catalyst According to the test data in Table 1: Compared with Example 2, the conversion rate of Example 1 after 1000h is about 23% higher. The difference between the two is that Example 1 adopts step-by-step impregnation, while Example 2 adopts one-time impregnation. The mechanism is mainly that in the step-by-step impregnation process, MnO x -CeO2 active layer is first loaded on the carrier to form a convex intermediate, and then the loaded CUO can not only x -CeO2 active layer combination not only increases the volume of the protruding intermediate, but also can further form composite active layer protrusions in the gaps between the protruding intermediates, such as Figure 3 As shown, the amount of transition metal oxides on the carrier is effectively increased. Since the transition metal oxides on the carrier are in the form of protrusions, the surface area of the catalyst on the fiber surface of the carrier is correspondingly increased, thereby being able to obtain higher reaction activity and more active sites, making the prepared catalyst more tolerant to silicon poisoning and increasing the service life of the catalyst. In addition, the active ingredients formed by distributed impregnation and covering the surface of the carrier are effectively guaranteed to be active because of the heating temperature during the heating process relative to one-time molding.
[0025] In Example 1, the silicon deposition capacity is about 6.7 times that of the comparative example, and the conversion rate after 1000h is about 2.4 times that of the comparative example. The main mechanism is that the three-dimensional mesh ceramic fiber cotton as a carrier has an order of magnitude increase in the specific surface area relative to the honeycomb ceramic. For example, the specific surface area of the honeycomb ceramic in the comparative example is generally about 10㎡ / g, while the specific surface area of the three-dimensional ceramic fiber cotton in Example 1 of the present application is 200-500㎡ / g. In addition, in the carrier of the specific proportion adopted, the addition of zirconium dioxide can further increase the specific surface area by about 20%, increase more contact area to improve the adhesion of the catalyst, and effectively enhance the high temperature stability of the catalyst, so that it can provide 5-10 times the silicon deposition capacity of the traditional catalyst, and the conversion rate is maintained>95% after continuous operation for 1000 hours at high temperature, and the pressure drop increases by <30%, which greatly improves the service life of the catalyst. In addition, the fiber mesh structure has a filtration retention rate of more than 90% for silicon deposits, which realizes the dynamic retention and capacity buffering of silicon deposits, and can effectively improve the performance of the catalyst as a pretreatment agent.
[0026] In summary, the fiber surface of the three-dimensional mesh ceramic fiber cotton prepared by the present invention is loaded with transition metal oxides, and the fiber surface catalyst preferentially converts organic silicon into silicon dioxide particles with a particle size of 0.1-1 μm, and uses a large specific surface area to provide a silicon deposition capacity 5-10 times that of traditional catalysts. At the same time, the fiber mesh structure has a filtration interception rate of more than 90% for silicon deposits, which realizes the dynamic interception and capacity buffering of silicon deposits, and improves the performance of the catalyst as a pretreatment agent. When the catalyst treats monosilane waste gas at 350°C, its service life can reach more than 5 times that of traditional catalysts, with significant economic benefits.
[0027] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other arbitrarily.
Claims
1. A method for preparing a silicon-poisoning resistant catalyst, characterized in that: include: S1, immersing high-aluminum ceramic fiber cotton in a zirconium acetate solution for aging treatment, filtering, drying, and calcining to form a three-dimensional mesh ceramic fiber cotton carrier composed of Al2O3-SiO2-ZrO2 composite oxide; S2, placing the carrier prepared in step S1 in a mixed solution of manganese nitrate and cerium nitrate, vacuum drying and calcining to form an intermediate, wherein the intermediate is a structure of the carrier fiber surface carrying the initial active layer, wherein the initial active layer is MnO x -CeO2; S3, placing the intermediate prepared in step S2 in a sealed container, evacuating the container, injecting copper sol and maintaining pressure, removing excess sol on the surface of the intermediate by centrifugation, and then drying and activating the intermediate to form a structure in which the fiber surface of the carrier is loaded with a transition metal oxide, wherein the transition metal oxide is MnO x -CeO2-CuO.
2. The method for preparing a silicon-poisoning resistant catalyst according to claim 1, characterized in that: In step S1, nitric acid is added to the zirconium acetate solution as a hydrolysis catalyst.
3. The method for preparing a silicon-poisoning resistant catalyst according to claim 1, characterized in that: In step S1, the fiber diameter in the carrier is 3 to 10 μm, the porosity is ≥ 85%, and the BET specific surface area is 200 to 500 m² / g.
4. The method for preparing a silicon-poisoning resistant catalyst according to claim 1, characterized in that: In step S1, the mass ratio of aluminum to silicon in the high-aluminum ceramic fiber wool is 6:
3.
5. The method for preparing a silicon-poisoning resistant catalyst according to claim 4, characterized in that: In step S1, the mass ratio of aluminum, silicon and zirconium in the carrier is 6:3:
1.
6. The method for preparing a silicon-poisoning resistant catalyst according to claim 1, characterized in that: In step S2, manganese nitrate (Mn(NO3)2·4H2O) and cerium nitrate (Ce(NO3)3·6H2O) are mixed at a molar ratio of Mn:Ce=4:1 and then prepared into a solution with deionized water.
7. The method for preparing a silicon-poisoning resistant catalyst according to claim 1, characterized in that: In step S3, the copper sol is formed by dissolving Cu(NO3)3·3H2O and citric acid in ethanol at a molar ratio of 1:1.
2.
8. The method for preparing a silicon-poisoning resistant catalyst according to claim 7, characterized in that: In step S3, drying activation is performed in the following manner: the intermediate with excess sol removed from the surface is dried at 120°C for 2 h, then heated to 600°C at a rate of 5°C / min, and reduced in a mixture of hydrogen and nitrogen for 2 h, wherein the volume ratio of hydrogen in the mixture of hydrogen and nitrogen is 5%.
9. A silicon-poisoning resistant catalyst, characterized in that: including a transition metal oxide supported on a carrier; The transition metal oxide is MnO x -CeO2-CuO, the mass fraction of the transition metal oxide is 15-20%; The carrier is a three-dimensional mesh ceramic fiber cotton composed of Al2O3-SiO2-ZrO2 composite oxide, the fiber diameter of the three-dimensional mesh ceramic fiber cotton is 3-10 μm, the porosity is ≥85%, and the BET specific surface area is 200-500 m2 / g.
10. The silicon-poisoning resistant catalyst according to claim 9, characterized in that: The mass ratio of aluminum, silicon and zirconium in the carrier is 6:3:1.
Citation Information
Patent Citations
Precious metal reduction catalyst for catalytic combustion of silicon-containing VOCs (Volatile Organic Compounds) as well as preparation method and application of noble metal reduction catalyst
CN118719124A
Oxidation Catalyst With Low CO and HC Light-Off and Systems and Methods
US20100166629A1
Exhaust gas purification catalyst with high resistance to silicon poisoning
US20150321185A1
Catalytic composite for purifying exhaust gases and a method for preparing the same
US5057482A